An ecological perspective on parents' experiences of having a child with autistic spectrum disorder (ASD) in the South African context. - Dawson, Nicola (My University, 2013)
Autistic Spectrum Disorder (ASD) has traditionally been understood and treated bio‐medically. However, bio‐ecological and eco‐systems theory, as well as a vast body of literature, suggests that ASD has a systemic impact, unique to each context. This study aimed to understand the systemic and ecological experiences of parents’ to children with ASD in the South African context with regard to ASD and ASD intervention. Eight parents to children with ASD were interviewed using a semi‐structured interview schedule. The data were analysed using deductive thematic content analysis. The study found that, in the South African context, both Indigenous and Western Knowledge Systems impact on parents’ experiences of having a child with ASD. It further found that ASD had a systemic impact, and that current ASD intervention failed to target the needs across the system. Lastly, it found that stigma originates from both Indigenous and Western Knowledge Systems, and that information about ASD is of great importance to parents in the South African context.
Keywords: Parents of autistic children--South Africa.; Autism spectrum disorders in children.